Simplified cell culture method for the diagnosis of atypical primary ciliary dyskinesia. Issue 12 (21st September 2009) - Pifferi, M; Montemurro, F; Cangiotti, A M; Ragazzo, V; Di Cicco, M; Vinci, B; Vozzi, G; Macchia, P; Boner, A L
Abstract : Background: The diagnosis of primary ciliary dyskinesia (PCD) can be challenging, and it may be particularly difficult to distinguish primary ciliary disease from the secondary changes after infections. Objectives: The purpose of the study was to evaluate if nasal epithelial cells, obtained with nasal brushing instead of a biopsy, could be used in a culture system for the diagnosis of PCD in difficult cases. Methods and main results: Ciliary motion analysis (CMA) and transmission electron microscopy (TEM) were performed on 59 subjects with persistent or recurrent pneumonia. These investigations allowed the diagnosis of PCD in 13 (22%) patients while the defect of the cilia was considered secondary to infections in 37 (63%) subjects. In the remaining nine (15%) patients the diagnostic evaluation with CMA and TEM remained inconclusive. Ciliogenesis in culture allowed the diagnosis of PCD in four of these patients, it was indicative of a secondary defect in two subjects, and it was not helpful in the remaining three patients. Conclusions: Culture of cells obtained with brushing of the nasal turbinate is not a perfect test, nevertheless it may offer diagnostic help in doubtful cases of PCD.